2010
DOI: 10.1158/1535-7163.mct-10-0625
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment with Silibinin and Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors Overcomes Drug Resistance Caused by T790M Mutation

Abstract: Although epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKI) produce an initially dramatic response in lung cancer patients harboring a mutation in the EGFR gene, development of acquired resistance is almost inevitable. A secondary mutation of threonine 790 (T790M) is associated with approximately half of the cases of acquired resistance. This study investigated whether the addition of silibinin to therapy with gefitinib or erlotinib could overcome T790M-mediated drug resistance considering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 36 publications
2
29
0
2
Order By: Relevance
“…Our results indicate that EGFR is a molecular target of DIM in ovarian cancer cells. Our results are in agreement with recent studies that showed that resveratrol, capsaicin, DIM, and silibinin suppress the growth of prostate, breast, and lung cancer cells by targeting EGFR (Stewart and O'Brian, 2004;Li et al, 2005;Ali et al, 2008;Rho et al, 2010;Thoennissen et al, 2010;Rajoria et al, 2011). Several pathways are affected by EGFR activation; MAPK is the main one.…”
Section: Discussionsupporting
confidence: 94%
“…Our results indicate that EGFR is a molecular target of DIM in ovarian cancer cells. Our results are in agreement with recent studies that showed that resveratrol, capsaicin, DIM, and silibinin suppress the growth of prostate, breast, and lung cancer cells by targeting EGFR (Stewart and O'Brian, 2004;Li et al, 2005;Ali et al, 2008;Rho et al, 2010;Thoennissen et al, 2010;Rajoria et al, 2011). Several pathways are affected by EGFR activation; MAPK is the main one.…”
Section: Discussionsupporting
confidence: 94%
“…We found that treatment with either agent was highly effective against multiple EGFR-mutant models in vitro (including PC9 and HCC827 cells with Del 19) (Figure 3A–B, Table S2). Moreover, GNS-1481 and GNS-1486 exhibited substantial efficacy in EGFR T790M -positive LA models in vitro , including PC-9/GR and PC-9/ER sub-lines with acquired resistance to gefitinib or erlotinib (33, 38), respectively, and H1975 cells that intrinsically harbor EGFR L858R/T790M (Figure 3A–B, Table S2). We further established the specificity of GNS-1481 and GNS-1486 efficacy for lung cancer cells with mutant EGFR by testing these agents in multiple EGFR WT lung cancer models, including A549, H460, and A341 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In line with previous research, both H1975 and PC-9GR cells harbor T790M mutation and show a higher level of EGFR activity than H1299 cells expressing wild-type EGFR, regardless of the presence of ligand EGF. This differential effect between cells with mutant and wild-type EGFR might be related to the cellular dependency for survival to EGFR signaling (24). The inhibitory effect of E + G combination surmounted the threshold that the cancer cells could tolerate.…”
Section: Discussionmentioning
confidence: 99%